The Effect of Oestradiol-17/β and Progesterone on the Pituitary Response to Gonadotrophin-Releasting Hormone (Gn-RH) in Anoestrous Ewes - SHAREHA, A. M. (The Libyan Journal of Agriculture, 2023)
The effect of progesterone (P) injection (2 X 12.5 mg/day) for 4 days and/or estra-diol—17/5 (E2—17/β The effect of progesterone (P) injection (2 X 12.5 mg/day) for 4 days and/or estra-diol—17/β(E2—17/β) infusion at a rate of 3 /ig/hr for 4 hours on the concentration of luteinizing hormone (LH) released by Gn-RH infusion (3 ^g/hr for 8 hours) was investigated in anoestrous ewes. The concentration of the LH released by Gn-RH was similar to that observed at oestrus. Sequential (P) and (E2—17/β) administration had no effect on LH release by Gn-RH, however, (E2—17/β) alone increased and (P) alone decreased the response.The effect of progesterone (P) injection (2 X 12.5 mg/day) for 4 days and/or estra-diol—17/5 (E2—17/β) infusion at a rate of 3 /ig/hr for 4 hours on the concentration of luteinizing hormone (LH) released by Gn-RH infusion (3 ^g/hr for 8 hours) was investigated in anoestrous ewes. The concentration of the LH released by Gn-RH was similar to that observed at oestrus. Sequential (P) and (E2—17/β) administration had no effect on LH release by Gn-RH, however, (E2—17/β) alone increased and (P) alone decreased the response.) infusion at a rate of 3 /ig/hr for 4 hours on the concentration of luteinizing hormone (LH) released by Gn-RH infusion (3 ^g/hr for 8 hours) was investigated in anoestrous ewes. The concentration of the LH released by Gn-RH was similar to that observed at oestrus. Sequential (P) and (E2—17/β) administration had no effect on LH release by Gn-RH, however, (E2—17/β) alone increased and (P) alone decreased the response.